Design and manufacturing of an automatic chiffon cake tin washing machine - Chan, Yee Ning (2015)
The purpose of this project is to improve the existing chiffon cake tin cleaning machine design, and then fabricate a functional prototype to test its feasibility. In the updated design, the core component performing the cleaning task is the rotary unit. Dirty cake tin will be released from a feeder system and drops on the center of the rotary platform, with the guidance of three rollers around. Two opposite water nozzles shoot out high pressure water jet tangentially towards the tin wall to create spinning motion on the cake tin together with the rotary platform. Spinning ensures the cake tin to be cleaned thoroughly. The rollers constrain the position of the cake tin, but also provide low friction during rotation. Finally, the water nozzle pointing inwards will be turned off. The washed cake tin will be pushed out of the platform by another water stream to a water tank and waiting to be collected, passing through a swing arm mounted with one of the roller. The arm turns outwards about a slightly slanted shaft when the cake tin breaks free, so it will return to its closed state under gravitational force and standby for the next cleaning. The rotary unit prototype was fabricated using PVC material by electrical hand tools and turning machine. Two flexible coolant nozzles are added to simulate the cleaning and ejection process in the test. The prototype test was then carried out using water source from a household water tap instead of an actual water jet system, since it was only a test for the device mechanism. Two methods of different water nozzles operating sequence were applied. After testing, the prototype was proved to be a workable design, as all the subcomponents on the device had served their functions well as expected in both methods. The success of the prototype test impelled the development of water jet cleaning method. The designs of other main components were refined and have to be fabricated and tested by the future students committed to this project.